Simultaneous Estimation of Atovaquone and Mefloquine Hydrochloride: QbD based Method Development and Validation - Sharma, Sanyam; Naman, Subh; Goyal, Kamya; Baldi, Ashish (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Atovaquone are important drugs that are used in the treatment of malaria and in combination with mefloquine hydrochloride increases the efficacy and potency. Present study covers the development of UV-spectrophotometry based analytical techniques for the simultaneous estimation of mefloquine HCl and atovaquone employing the Quality by Design (QbD) methods. Materials and Methods: C-N-X method were employed for risk assessment study and Ishikawa fishbone diagram was plotted for understanding of various factors that affect method development. Central Composite Design (CCD) was utilized for selected significant factors optimization. Scanning speed and scanning interval were considered as independent variables and absorption at 222 nm and 251 nm were considered as responses. Response surface plots and design space were developed for mathematical modelling-based prediction of responses obtained within specified ranges and optimization. Developed simultaneous analytical method was further validated as per the ICH Q2 guidelines. Results: The method showed good linearity with R2 > 0.9 and good recovery with % RSD less than 2. The LOD and LOQ of UV developed method was found to be satisfactory and well between the acceptable range. Conclusion: The developed method for simultaneous estimation of atovaquone and mefloquine hydrochloride may act as a quick, precise, accurate, and economical quality control method for regular and simultaneous estimation of atovaquone and mefloquine HCl in bulk and mixed dosage forms at industrial level.
Keywords: Accuracy; Analytical Method Development; ICH Q2 guidelines; Precision; Quality by Design; Risk Assessment